Radiosynthesis and evaluation of new PET ligands for peripheral cannabinoid receptor type 1 imaging. Issue 17 (1st September 2017) - Yamasaki, Tomoteru; Fujinaga, Masayuki; Shimoda, Yoko; Mori, Wakana; Zhang, Yiding; Wakizaka, Hidekatsu; Ogawa, Masanao; Zhang, Ming-Rong
Graphical abstract: Highlights: We successfully developed new CB1-PET ligands [ 11 C]2 and [ 11 C]3 using [ 11 C]COCl2 . In vitro profile of [ 11 C]2 was superior to that of [ 11 C]3 . PET with [ 11 C]2 demonstrated high specific binding to CB1 in the BAT of mouse. Abstract: Cannabinoid receptor type 1 (CB1) is mainly expressed in the brain, as well as being expressed in functional relevant concentrations in various peripheral tissues. 1-(4-Chlorophenyl)-3-(3-(6-(pyrrolidin-1-yl)pyridin-2-yl)phenyl)urea (PSNCBAM-1, 1 ) was developed as a potent allosteric antagonist for CB1 and its oral administration led to reductions in the appetite and body weight of rats. Several analogs of1 (compounds2 and3 ) were recently identified through a series of structure-activity relationship studies. Herein, we report the synthesis of radiolabeled analogs of these compounds using [ 11 C]COCl2 and an evaluation of their potential as PET ligands for CB1 imaging using in vitro and in vivo techniques. [ 11 C]2 and [ 11 C]3 were successfully synthesized in two steps using [ 11 C]COCl2 . The radiochemical yields of [ 11 C]2 and [ 11 C]3 were 17 ± 8% and 20 ± 9% (decay-corrected to the end of bombardment, based on [ 11 C]CO2 ). The specific activities of [ 11 C]2 and [ 11 C]3 were 42 ± 36 and 37 ± 13 GBq/μmol, respectively. The results of an in vitro binding assay using brown adipose tissue (BAT) homogenate showed that the binding affinity of2 for CB1 ( K D = 15.3 µM) was much higher than that of3 (KD = 26.0 µM). PET studies with [ 11 C]2 showed a high uptake of radioactivity in BAT, which decreased in animals pretreated with AM281 (a selective antagonist for CB1). In conclusion, [ 11 C]2 may be a useful PET ligand for imaging peripheral CB1 in BAT.